Dialogization of education during practical exercises and seminars of future teachers of philological specialties as a condition of the formation of didactic competence. (Pedagogy of Higher and Secondary Education, 2013)
Mishenina T. М. Dialogization of education during practical exercises and seminars of future teachers of philological specialties as a condition of the formation of didactic competence.The article reveals the essence of the concept of «learning dialogization»; dialogization justified as a didactic training for building a didactic competence of future teachers philological specialties. Lightened aspectual components didactic discourse in humanitarian training of future professionals.
Keywords: dialogization learning iseminarskoe practical lessons; future teachers philological specialties; didactic discourse; teaching competence